ENTREPRENEURIAL CHARACTERISTICS OF BETAWI BATIK WOMEN ACTIVISTS - Iedarwati, Pradewi (Universitas Ciputra Surabaya, 2017)
Batik industry, including Betawi Batik, ever experienced a gloomy period due to the rise of modern textile industry. Fortunately, this industry has raised again after UNESCO states that Batik is one of the Indonesian cultural heritages. The government of DKI Jakarta with Betawi Cultural Institution initiate to popularize Batik Betawi by establishing Batik Betawi Family (or KKB). Since 2012, KBB has succeeded in producing studios in Jabodetabek area, which are mostly driven by women. Entrepreneurial characteristic can become a factor affecting the growth and development of Batik studios as an effort to grow and preserve Batik Betawi. This study aims to identify the characteristics of woman entrepreneurship as Betawi Batik activist. This research uses phenomenology approach to explain how a person gives meaning and interprets actions that are done related to her business activity. Respondents are determined using purposive sampling technique, and data are collected through conducting interviews on three women as activists of Batik Tarogong, Batik Gandaria and Batik Rusunawa Marunda. The triangulation results identify five characteristics of Batik woman entrepreneur: (1) can relate well with others, (2) honest and respect others’ rights, 3) capable to run a business, (4) open to criticism and suggestions, and (5) have a willing to learn from mistakes. These five characteristics include three dimensions of entrepreneurial characteristics namely personality dimension, managerial dimension and agent of change dimension.